2022
DOI: 10.1039/d2nj02174a
|View full text |Cite
|
Sign up to set email alerts
|

Citrate capped silver nanoparticles as an instantaneous colorimetric selective sensor for neomycin and thiamine in wastewater

Abstract: As the usage of antibiotics and vitamin tablets become more widespread, detrimental impacts on living beings are increasing by swallowing polluted water contaminated with drug residues. Because of the emergence...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Furthermore, coating SiO 2 NPs with Ag, yttrium oxide (Y 2 O 3 ), and ZnO showed improved biocompatibility. Based on biomedical studies, it has been reported that the Ag NPs while traveling along the blood stream accumulate in different body tissues and organs, making these organs susceptible to damage and altering the physiological functions. , However, when compared to other NPs, Ag NPs are more accessible due to their room temperature stability as well as their affordable precursors . Despite the toxic impacts, aqueous solution of Ag NPs deposited in different media such as SiO 2 or composites has been used as an effective sterilizing tool in agriculture and veterinary practices. , The effectiveness and efficiency of the NPs are increased in a specific treated atmosphere through a variety of methods of modification. It has been reported that Ag and SiO 2 NPs behave differently in biological systems, while studies have also indicated that SiO 2 -coated Ag NPs are less toxic than individual Ag NPs, but Ag-SiO 2 NPs have not been investigated in detail when compared to SiO 2 or Ag NPs separately.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, coating SiO 2 NPs with Ag, yttrium oxide (Y 2 O 3 ), and ZnO showed improved biocompatibility. Based on biomedical studies, it has been reported that the Ag NPs while traveling along the blood stream accumulate in different body tissues and organs, making these organs susceptible to damage and altering the physiological functions. , However, when compared to other NPs, Ag NPs are more accessible due to their room temperature stability as well as their affordable precursors . Despite the toxic impacts, aqueous solution of Ag NPs deposited in different media such as SiO 2 or composites has been used as an effective sterilizing tool in agriculture and veterinary practices. , The effectiveness and efficiency of the NPs are increased in a specific treated atmosphere through a variety of methods of modification. It has been reported that Ag and SiO 2 NPs behave differently in biological systems, while studies have also indicated that SiO 2 -coated Ag NPs are less toxic than individual Ag NPs, but Ag-SiO 2 NPs have not been investigated in detail when compared to SiO 2 or Ag NPs separately.…”
Section: Introductionmentioning
confidence: 99%
“… 16 , 17 However, when compared to other NPs, Ag NPs are more accessible due to their room temperature stability as well as their affordable precursors. 18 Despite the toxic impacts, aqueous solution of Ag NPs deposited in different media such as SiO 2 or composites has been used as an effective sterilizing tool in agriculture and veterinary practices. 19 , 20 The effectiveness and efficiency of the NPs are increased in a specific treated atmosphere through a variety of methods of modification.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are consistent with a previous report demonstrating the complexation between citrate ligands on AgNP surfaces and nitrogen functionalities of AGs, resulting in AgNP aggregation. 42 Peptides rich in arginine residues have been utilized to prepare AG derivatives, such as tri-argininegentamicin and tetra-arginine-kanamycin, through the conjugation of carboxyl groups of amino acids with NH 2 groups of AGs. 54,90 Moreover, the conjugation of biomolecules, including amino acids, peptides, and nucleic acids, with AGs is emerging as a promising strategy in the biomedical field.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The application of SPR as nanosensors provides several benefits, including high selectivity, sensitivity, portability, and potential for the rapid and reliable detection of target analytes . Among the metal NPs, silver nanoparticles (AgNPs) have been extensively investigated as colorimetric assays and utilized as low-cost nanoprobes for the detection of antibiotics. Likewise, label-free colorimetric assays based on gold nanoparticles (AuNPs) have been developed for the detection of antibiotics. ,, The aggregation-induced color change and spectral shifts of metal NPs in the presence of target antibiotics enable rapid and sensitive detection. Moreover, besides colorimetric sensing, other types of sensors based on changes in magnetic properties and electrochemical systems have also been demonstrated for the detection of antibiotics. Additionally, surface-enhanced Raman scattering (SERS) techniques, which rely on the enhancement of Raman signals using metal NPs, have shown great potential for antibiotic detection. The recent advances in metal NP-based sensing strategies have contributed to the development of practical analytical tools for detecting antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of AgNPs was carried out according to previous literature with minor changes. 29,30 Briey, 100 mL of 0.1 M trisodium citrate was stirred in an ice bath at about 5 °C for 15 minutes. Next, 2 mL of 0.005 M AgNO 3 solution was added dropwise to the citrate solution while maintaining consistent stirring for about 5 minutes, and the solution was stirred for another 10 minutes to acquire awless capping of citrate over silver ions.…”
Section: Preparation Of Silver Nanoparticles (Agnps)mentioning
confidence: 99%